Preparation of Project-Based Learning Tools to Strengthen Pancasila Student Profiles (P5) - Asma'ul Husna; Iswari Maulinda; Annisa Cahyani; Husnul Khatimah; Niswatul Fitriani; Elmilia Husaini; Mijahamuddin Alwi (Future Tecno-Science Publisher, 2025)
This educational assistance program is an ongoing effort in which various stakeholders collaborate to achieve better educational outcomes for the community. The school curriculum's project-based learning tools to strengthen Pancasila values (P5) will be implemented for the current phase. It is necessary to provide guidance for teachers in developing these materials. Currently, only 20% of the teachers at this school understand the implementation of P5, while the remainder have not yet gained any understanding of it. The purpose of this activity is to equip and support teachers so they can develop suitable learning tools. One of the benefits teachers gain from this assistance is a refreshing of their knowledge. This benefit has a positive impact and is certain to improve the quality of the school in the future.